Treatable traits in idiopathic pulmonary fibrosis: focus on respiratory tract infections—a systematic review and a meta-analysisResearch in context - Zsombor Matics; Anna Bardóczi; Csongor Galkó; Bence Szabó; Noémi Gede; Zsolt Molnár; Gábor Duray; Caner Turan; Péter Hegyi; Gábor Horváth; Veronika Müller (EClinicalMedicine)
Summary: Background: Idiopathic pulmonary fibrosis (IPF) is a progressive, deadly lung disease with several factors, including respiratory tract infections (RTI), for disease worsening. There's no comprehensive data on RTI incidence in IPF patients across different therapies, including antifibrotic (nintedanib or pirfenidone), investigative or placebo treatments. Methods: A systematic search of databases Medline, EMBASE, Cochrane Central, Web of Science and Scopus was conducted on September 30th 2024 (PROSPERO registration number: CRD42023484213). Only randomized controlled trials of drugs intended for IPF treatment in adults and reporting RTI incidence were included. Pooled risk ratio with 95% confidence interval (CI), risk of bias, GRADE and CINEMA assessments were conducted along with subgroup analyses for upper and lower RTI and for different antifibrotic doses. Findings: A total of 27 trials of different drugs aimed for IPF therapy were pooled in a pairwise meta-analysis, 11,542 patients were analyzed with an overall number of 4156 RTI events, representing an average incidence of 38.4 ± 23.5%. Most therapies did not affect RTI risk in IPF, although single trials with everolimus and trimethoprim/sulfamethoxazole showed a significant decrease compared to placebo. For antifibrotics, RTI incidence was similar with pirfenidone treatment compared to nintedanib (RR: 0.98 CI: [0.71; 1.36]) and compared to placebo (RR: 0.88 CI: [0.69; 1.10]) and nintedanib compared to placebo (RR: 0.89 CI: [0.71; 1.12]). Interpretation: RTIs are frequently reported adverse events in IPF patients over a one-year period, with different investigated treatments showing no profound impact compared to placebo. Future clinical trials should focus on targeting treatable traits like RTIs. Funding: None.